Pengembangan LKPD IPAS Berbasis Problem Based Learning Materi Perubahan Iklim di Kelas IV UPTD SDN Demangan 1 Bangkalan - Siti Madiah Ulfa; Isna Ida Mardiyana (Mataram University, 2026)
Science and Social Studies (IPAS) learning on the topic of climate change requires instructional materials that actively engage students in solving contextual problems. This study aimed to determine the validity, effectiveness, and attractiveness of an IPAS Student Worksheet (LKPD) based on the Problem-Based Learning (PBL) model on climate change material for fourth-grade elementary school students. The study employed a Research and Development (R&D) method using the 4D development model, which consists of the define, design, develop, and disseminate stages. The research subjects were fourth-grade students of UPTD SDN Demangan 1 Bangkalan in the 2025/2026 academic year. The research instruments included expert validation sheets, teacher and student activity observation sheets, learning achievement tests, and teacher and student response questionnaires. The results indicated that the developed LKPD met the criteria of being valid, effective, and highly attractive. The validity scores were 77% from instructional material experts, 77% from subject matter experts, and 94% from instructional design experts. The effectiveness was demonstrated by teacher activity scores of 84.5% in the limited trial and 88.5% in the implementation trial, student activity scores of 81.5% and 81%, and classical learning mastery of 100% and 89%, respectively. The attractiveness of the product was reflected in teacher response scores of 100% and student response scores of 92% in the limited trial and 93% in the implementation trial. Therefore, the PBL-based IPAS Student Worksheet is feasible for use in elementary school IPAS learning.